2023
DOI: 10.3390/cimb45080409
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug Resistance Profiles and Resistance Mechanisms to β-Lactams and Fluoroquinolones in Bacterial Isolates from Hospital Wastewater in Bangladesh

Abstract: Multidrug resistance (MDR) is one of the deadliest public health concerns of the 21st century, rendering many powerful antibiotics ineffective. The current study provides important insights into the prevalence and mechanisms of antibiotic resistance in hospital wastewater isolates. In this study, we determined the MDR profile of 68 bacterial isolates collected from five different hospitals in Dhaka, Bangladesh. Of them, 48 bacterial isolates were identified as Enterobacteriaceae. Additionally, we investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…Similar resistant genes ( gyrA_ S83L, gyrA_ D87N, parC_ S80I, and parE_ S458A) identified from this study in presumptively healthy children have been reported in disease cases of children admitted to hospitals in Bangladesh and Benin [ 43 , 44 ]. The presence of these enteric pathogens isolated from presumptive healthy children is of great concern as these children serve as potential reservoirs for transmission of these pathogens to other susceptible individuals.…”
Section: Discussionsupporting
confidence: 81%
“…Similar resistant genes ( gyrA_ S83L, gyrA_ D87N, parC_ S80I, and parE_ S458A) identified from this study in presumptively healthy children have been reported in disease cases of children admitted to hospitals in Bangladesh and Benin [ 43 , 44 ]. The presence of these enteric pathogens isolated from presumptive healthy children is of great concern as these children serve as potential reservoirs for transmission of these pathogens to other susceptible individuals.…”
Section: Discussionsupporting
confidence: 81%
“…The spread pattern of Multiple drug resistance (MDR) explores a threatening risk for human boosting up morbidity, mortality and cost. 12 Untreated waste water may facilitate more spread of multi drug resistance (MDR). In the present study, the physico-chemical parameters of collected samples were measured and the results of the physico-chemical parameters of collected samples are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…11 Not only that, several virulence factors are spread out due to multidrug resistance (MDR) in health care centers and others community settings impacting economic and social aspects, less productivity and high poverty rate. 12 Considering the concerning fact relating to multidrug resistance of P. aeruginosa, the present study was designed to isolate and identify environmental P. aeruginosa from 2 types of waste water samples and show their antibiotic resistance pattern. Besides, pH, temperature, DO (Dissolve Oxygen), TDS (Total Dissolve Solids), TVC (Total Viable Count), TC (Total Coliform) of the collected water samples were also documented as well.…”
Section: Introductionmentioning
confidence: 99%